The Relationship between Using Gadgets and Speaking Ability of Preschool Children in the Working Area of the Air Putih Public Health Center, Samarinda City - Putri, Radinka Audrey; Sutrisno, Sutrisno; Widiastuti, Hesti Prawita (JURNAL IBU DAN ANAK, 2023)
Preschool children are children aged 3-6 years, at this time the ability of skills, thinking and activities of children increases and their growth is stable. The ability to speak is the expression of ideas he thinks about and himself in the form of words or the pronunciation of certain sounds. Use of gadgets is a child who plays using gadgets for more than 30 minutes and once a day. This type of quantitative descriptive research with a retrospective study design and cross sectional approach. The sample size was determined by means of probability sampling with a proportionate stratified random sampling technique, with a total sample of 162 respondents. Data analysis used is chi-square. Bivariate analysis found a relationship between the use of gadgets and the speaking ability of preschool children (p-value = 0.002), which means that there is a significant relationship between the use of gadgets and the speaking ability of preschool children in the Working Area of ​​the Air Putih Public Health Center, Samarinda City.